Extraterritoriality and Criminal Law: from Unilateral Action to a Multilateral Paradigm. - Bautista-Hernáez, Andrés (Brill-Nijhoff, 2022)
Much of the thinking about the extraterritoriality of criminal law remains within the paradigm of unilateral actions by States. This paradigm starts with the principle of strict territoriality, that is to say, no State can take action to enforce its laws outside its own borders. So, within this paradigm, the conversation is always about whether a State has an appropriate jurisdictional basis to act, and the nature of the limits on that action supplied by International Law. Today, however, the prosecution of state criminal law in cases with cross-border elements frequently takes place not within a paradigm of unilateral action but rather within a multilateral paradigm. For instance, many States have entered into bilateral mutual legal assistance treaties. Under these treaties, States may enlist the assistance of their treaty partners in taking certain enforcement actions overseas, thus getting around the traditional territorial limitation on enforcement. Equally important, there are now multilateral treaties in many critical areas, such as anti-corruption and money laundering or human right violations such as female genital mutilation, that actively require member states to prosecute certain crimes with cross-border elements, thus legitimizing the jurisdiction of States to apply their criminal laws to foreign conduct. This chapter will investigate the shift from the traditional unilateral paradigm to this more multilateral approach and ask what it means for our understanding of extraterritoriality.
Versión postprint. https://brill.com/page/419324
Keywords: Extraterritorialidad; Derecho internacional público; Derecho internacional penal; Extranjeros; Derecho penal